Design And Develop A Mobile-Based Tour Guide Application In Purwakarta City - Nuraprian, Nina; Defriani, Meriska; Singasatia, Dayan (RISTEC : Research in Information Systems and Technology, 2021)
Abstract Puwrakarta City is one the regencies in West Java that is currently developing. Purwakarta city is located in a geographical area thatis rich in natural attraction, culinary tourism, and cultural tourism so that the city of Purwakarta become a tourist attractio, but not all tourist attractions in the city of purwakarta are know by local tourists and tourists outside the srea who want to visit and the lack of information anda there are many remote areas which are very unfortunate to miss its tourist attraction. Therefore, a mobile-based tourism application was made to make it easier for tourists to find tours. This software development uses the waterfall method to the dev stage, software modeling uses the Unified modeling Language (UML) modeling which consists of 4 stage, namely use case diagrams, activity diagrams, sequence diagrams, and class diagrams, with programming language using Dart, Firebase database, and using Flutter. This research produces a mobile-based application that has information about natural tourism, culinary tourism, and cultural tourism to that it can be used to disseminate between locak tourists and tourists outside the area in Purwakarta City.